Self-Assembled Biocompatible Fluorescent Nanoparticles for Bioimaging - Caponetti, Valeria; Trzcinski, Jakub W.; Cantelli, Andrea; Tavano, Regina; Papini, Emanuele; Mancin, Fabrizio; Montalti, Marco (Frontiers in Chemistry, 2019)
Fluorescence is a powerful tool for mapping biological events in real-time with high special resolution. To achieve high sensitivity ultra-bright probes are needed that collect in a single nanoparticle a huge number of fluorophores. Unfortunately this assembly results in the quenching of the fluorescence because of short-range intermolecular interaction. He we demonstrate that rational structural modification of a well-known molecular fluorophore N-(7-Nitrobenz-2-oxa-1,3-diazol-4-yl) (NBD) produce a molecule that self-assemble in nanoparticles in biocompatible environment without any dramatic decrease of the fluorescence brightness. The resulting NPs show a brightness which is more than 6 orders of magnitude higher than the molecular component. Moreover, beside the particle are prepared by nanoprecipiation and they are stabilized only via non covalent interaction they are surprisingly stable and can be observed as individual bright spots freely diffusing in solution at a concentration as low as 1 nM. The suitability of the NP as biocompatible fluorescent probes was demonstrated in the case of HeLa cells by fluorescence confocal microscopy and MTS assays.